2012
DOI: 10.1590/s1806-37132012000500016
|View full text |Cite
|
Sign up to set email alerts
|

O tórax e o envelhecimento: manifestações radiológicas

Abstract: In the elderly (conventionally defined as individuals ≥ 60 years of age), it is often difficult to establish what normality is, because of the numerous anatomical and physiological modifications that occur during the aging process. As a result, the greatest challenge is to differentiate between the normal aging process and the onset of disease. Healthy elderly people commonly present borderline findings on chest imaging. We systematically reviewed the medical literature on the subject, covering the period betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…With the increased life expectancy, the elderly population presents changes in the respiratory system 2 , presenting among them changes in lung complacency and parenchyma 2,3 and respiratory muscle strength 4 . The performance of respiratory muscles is related to modifications of the chest cavity caused by aging 2 , which causes malfunction of the diaphragm because, the principle of muscle length and tension will not occur in an adequate way 5 .…”
Section: Introductionmentioning
confidence: 99%
“…With the increased life expectancy, the elderly population presents changes in the respiratory system 2 , presenting among them changes in lung complacency and parenchyma 2,3 and respiratory muscle strength 4 . The performance of respiratory muscles is related to modifications of the chest cavity caused by aging 2 , which causes malfunction of the diaphragm because, the principle of muscle length and tension will not occur in an adequate way 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al showed an increased air trapping with age [19]. The frequent finding of small basal atelectasis in asymptomatic elderly patients has been reported [20]. Further morphological changes with ageing are progressive calcifications of the airways and the rib cage [15, 16, 20] (Figure 3).…”
Section: Changes Of the Lungs With Ageingmentioning
confidence: 99%
“…The reduced mass of other thoracic muscles has been described but has not been studied in detail [20]. …”
Section: Changes Of the Lungs With Ageingmentioning
confidence: 99%
“…al. 6 described how age affects radiograph findings and how to differentiate between the normal aging process and the onset of diseases. The scarcity of work is likely because, as a cheaper and quick imaging exam, CXRs are more often used for triaging and screening than final diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%